Partnering on vaccines to counter multi-drug resistant threats: Workshop proceedings, Biomedical Advanced Research and Development Authority - Julie N. Bergmann; Rushyannah R. Killen-Cade; Lindsay A. Parish; Mark T. Albrecht; Daniel N. Wolfe (Taylor & Francis Group, 2022)
On March 12, 2021, the Biomedical Advanced Research and Development Authority (BARDA) sponsored a virtual market research workshop, "Partnering on Vaccines to Counter Multi-Drug Resistant Threats," to discuss the threat of antimicrobial resistance in the context of BARDA's mission space and the challenges encountered during the development of vaccines for specific antimicrobial resistant bacteria. The workshop convened representatives with expertise in vaccine development from government, academia, and industry. This report summarizes the presentations and subsequent discussions from the workshop and highlights existing challenges to advance the development of vaccine candidates for antimicrobial resistant pathogens, including Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Staphylococcus aureus.